Analisis Pengaruh Bauran Pemasaran terhadap Perilaku Konsumen Kopi (Studi Kasus: Konsumen Kedai Kopi di Desa Condong Catur Kecamatan Depok Kabupaten Sleman) - Rosyadi, Muhammad As’ad; Suswatiningsih, Tri Endar; Ambarsari, Arum (Program Studi Agribisnis INSTIPER Yogyakarta, 2025)
This research aims to determine the characteristics of coffee shop consumers, the ap This research aims to determine the characteristics of coffee shop consumers, the application of marketing mix components, and the influence of these components on consumer behavior at coffee shops in Condongcatur Village. The location for the study was deliberately chosen (purposive sampling). The research was conducted in three coffee shops: Samasta Coffee, Jempolan Coffee, and Tilasawa Coffee Roaster. The sampling method used was Accidental Sampling. The total sample size for this study was 45 respondents. Data analysis was conducted using multiple linear regression analysis. The results of this study indicate that the characteristics of coffee shop consumers are predominantly male, with an average age of 25 years, primarily students. The average distance from home to the coffee shop is 4.7 km, with an average frequency of visits of 2 times per month. Among the three coffee shops studied, Jempolan Coffee had the best implementation of marketing mix components. Furthermore, the marketing mix did not have a significant effect on price, promotion, product, and place.